Scoping study to identify capacity and needs of emerging leaders (men, women, and youth) for strengthening WEFE nexus approach Uzbekistan - Namozov, Orifjan; Babajanova, Zukhra; Sin, Liliana; Djumanazarova, Aygul (2024)
The presentation highlights following 4 points: 1. NEXUS GAINS Work Package 5 2. Theory of change in capacity-building interventions in the WEFE sector 3. Review of the capacity-building policies for strengthening WEFE nexus in Uzbekistan 4. Assessment of the capacity and needs of WEFE Actors (men, women, and youth) in Uzbekistan